Efektivitas Program GEMES (Gerakan Media Sehat) untuk meningkatkan pengetahuan ibu dan kader di Posyandu Buah Hati Bunda Samarinda - Sefia Diva Febriani; Anifa Temongmere; Arniah; Dhiya Talitha; Evana Dhiyalanni; Nabilla; Nurjanah; Ririn Arianti; Wanda Dila Vionita; Nur Rohmah; Lies Permana; Annisa Nurrachmawati; Rina Tri Agustini (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2025)
The Effectiveness of the GEMES Program (Healthy Media Movement) in Improving the Knowledge of Mothers and Cadres at Posyandu Buah Hati Bunda in Samarinda. Posyandu is an essential primary healthcare service that plays a crucial role in supporting maternal and child health. However, low community participation in Posyandu Buah Hati Bunda is due to a lack of understanding among mothers about the importance of Posyandu and the services it provides. To address this issue, training was conducted for Posyandu cadres on creating informative and engaging posters. This activity aimed to enhance the cadres’ skills in delivering health information and increase community participation. The training used the Canva design application and involved Posyandu cadres, neighborhood leaders, and mothers with infants and toddlers in RT 13, Lok Bahu Village, Samarinda. Pre-test and post-test evaluations showed a significant improvement in mothers’ understanding of the importance of Posyandu after receiving education through the posters. The posters produced are not only used as an educational medium but are also planned to be routinely distributed through digital media and displayed in strategic locations. This program demonstrates that enhancing Posyandu cadres’ skills in creating effective informational media can raise community awareness, support the success of Posyandu activities, and improve maternal and child health.